Penerapan Inovasi Teknologi Guna Meningkatkan Mutu dan Produksi Keripik Pisang Di Desa Pakuan - Ayu, Hanifah; Rahmat Sabani; Ansar; Murad; Surya Abdul Muttalib (Universitas Mataram, 2025)
A surplus of bananas in Pakuan Village has led the local community to process them into various banana-based products, one of which is banana chips. Banana chips are a processed food product with significant potential as a source of income for the people of Pakuan Village. However, the quality and production capacity of banana chips in the village still face several challenges, such as traditional and inefficient production processes, resulting in suboptimal product quality and limited production volume. The purpose of this community service activity is to conduct direct observation and apply technological innovations in the banana chip production process as an effort to improve both product quality and quantity. The method employed in this activity involves providing training and education to enhance skills in the application of technological innovations through hands-on practice, particularly using an oil-draining machine in the banana chip production process. The implementation of this appropriate technology has proven to be highly effective and efficient in improving the quality and production of banana chips in Pakuan Village, ultimately contributing to the welfare of the local community and increasing the competitiveness of the products in the market.